CORN ROOT LENGTH DENSITY AND ROOT DIAMETER AS AFFECTED BY SOIL COMPACTION AND SOIL WATER CONTENT - Duruoha, Charles; Piffer, Cassio Roberto; Silva, Paulo Arbex (IRRIGA, 2007)
CORN ROOT LENGTH DENSITY AND ROOT DIAMETER AS AFFECTED BY SOIL COMPACTION AND SOIL WATER CONTENT Charles Duruoha1; Cassio Roberto Piffer2; Paulo Arbex Silva2 (1) United States Department of Agriculture (USDA-ARS), National Soil Dynamics Laboratory, Auburn, AL - U.S.A, duruohan@juno.com (2) Universidade Estadual Paulista, Faculdade de Ciências Agronômicas, Departamento de Engenharia Rural, Botucatu, SP 1 ABSTRACT Negative effects of soil compaction have been recognized as one of the problems restricting the root system and consequently impairing yields, especially in the Southern Coastal Plain of the USA. Simulations of the root restricting layers in green house studies are necessary for the development of mechanism which alleviates soil compaction problems in these soils. The selection of three distinct bulk densities based on the standard proctor test is also an important factor to determine which bulk density restricts the root layer. The experiment was conducted to assess the root length density and root diameter of the corn (Zea mays L.) crop as a function of bulk density and water stress, characterized by the soil density (1.2; 1.4, and 1.6 g cm-3), and two levels of the water content, approximately (70 and 90% field capacity). The statistical design adopted was completely randomized design, with four replicates in a factorial pattern of (3 x 2). The PVC tubes were superimposed with an internal diameter of 20 cm with a height of 40 cm (the upper tube 20 cm, compacted and inferior tube 10 cm), the hardpan with different levels of soil compaction were located between 20 and 30 cm of the depth of the pot. Results showed that: the main effects of subsoil mechanical impedance were observed on the top layer indicating that the plants had to penetrate beyond the favorable soil conditions before root growth was affected from 3.16; 2.41 to 1.37 cm cm-3 (P<0.005). There was a significant difference at the hardpan layer for the two levels of water and 90% field capacity reduced the root growth from 0.91 to 0.60 cm cm-3 (P<0.005). The root length density and root diameter were affected by increasing soil bulk density from 1.2 to 1.6 g cm-3 which caused penetration resistance to increase to 1.4 MPa. Soil water content of 70% field capacity furnished better root growth in all the layers studied. The increase in root length density resulted in increased root volume. It can also be concluded that the effect of soil compaction impaired the root diameter mostly at the hardpan layer. Soil temperature had detrimental effect on the root growth mostly with higher bulk densities. KEYWORDS: Soil compaction, water, bulk density, soil strength, root growth. DURUOHA, C.; PIFFER, C. R.; SILVA, P. A. COMPRIMENTO E DIÂMETRO RADICULAR DO MILHO, EM FUNÇÃO DA COMPACTAÇÃO E DO TEOR DE ÁGUA NO SOLO 2 RESUMO Os efeitos negativos da compactação do solo vêm sendo reconhecidos como um dos problemas que restringe o sistema radicular e conseqüentemente, impede a produção agrícola, especialmente no sudoeste dos Estados Unidos. Simulações de camadas de restrição de raízes, em casa de vegetação, são necessárias para desenvolver mecanismos que reduzam problemas de compactação dos solos. A seleção de três diferentes densidades de solo, baseadas no ensaio de Proctor é também um fator importante para determinar qual densidade restringe a penetração da raiz. O experimento foi conduzido para avaliar o comprimento e diâmetro radicular da cultura do milho (Zea mays L.), em função da densidade do solo e do estresse hídrico, caracterizado pelas densidades (1,2; 1,4 e 1,6 cm-3) e dois níveis de teor de água (70 e 90 % da capacidade de campo). O método estatístico utilizado foi inteiramente casualizado, com quatro repetições, em arranjo fatorial (3 x 2). Os vasos foram montados em tubos de PVC, com diâmetro interno de 20 cm, sobrepostos, totalizando 40 cm de altura (anel superior com 20 cm e anéis compactado e inferior com 10 cm), a camada com diferentes níveis de solo compactado foi instalada entre 20 e 30 cm de profundidade nos vasos. Os resultados indicaram, através da resistência mecânica que na camada superior as raízes conseguiram penetrar até onde havia condições favoráveis do solo, antes que o sistema radicular fosse afetado de 3,16; 2,41 e 1,37 cm cm-3 (P<0.005). Ocorreu diferença significativa na camada compactada para os dois níveis de teor de água, sendo que a 90 % da capacidade de campo houve uma redução do crescimento radicular de 0,91 para 0,60 cm cm-3 (P<0,005). O comprimento e o diâmetro radicular foram afetados pelo aumento da densidade do solo de 1,2 a 1,6 g cm-3, com resistência à penetração de 1.4 MPa. O teor de água de 70 % da capacidade de campo proporcionou maior comprimento radicular em todas as densidades estudadas. O aumento no comprimento radicular resultou em maior volume radicular. Concluiu-se também que os efeitos da compactação do solo prejudicaram o diâmetro radicular, principalmente na camada compactada. A temperatura do solo afetou o crescimento radicular, principalmente nas camadas com densidade elevada. UNITERMOS: compactação do solo, teor de água, densidade do solo, resistência à penetração, crescimento radicular.